The mechanical action of powerful energy fluxes upon the high porous heterogeneous material - Efremov, V.P.; Ostrik, A.V.; Potapenko, A.I.; Fortov, V.E. (Вопросы атомной науки и техники, 2000)
The development of new particle boosters requires new models, describing of behavior of powerful beam interaction with heterogeneous insulator materials. The method of thermal properties determination of high porous material, irradiated by powerful electron and X-ray beam was developed. The differential equation of state for porous matter was used. The powerful flux action upon various material types is numerically studied. Calculated data are compared with experimental one.